T168. MACULAR THINNING IN FEMALE PATIENTS WITH PSYCHOSIS SPECTRUM DISORDERS: PRELIMINARY OPTICAL COHERENCE TOMOGRAPHY FINDINGS. (18th May 2020) - Jerotic, Stefan; Ristic, Ivan; Ignjatovic, Zora; Maric, Nadja
Abstract: Background: Structural retinal architecture in living organisms became measurable with the development of optical coherence tomography (OCT) scanners. Recent investigations identified thinning of individual retinal layers in psychosis spectrum disorders (PSD) [1]. Previous reports have shown that structural sex dimorphism of normal brain development is disturbed in psychosis [2]. To the best of our knowledge, no study has examined sex differences in retinal architecture in PSD. Methods: A total of 39 patients with psychosis spectrum disorders and 35 healthy controls matched by age and sex were included. The groups were further divided according to sex: male patients (MP; n=21), female patients (FP; n=18), male controls (MC; n=18), female controls (FC; n=17). A spectral-domain OCT device (Cirrus 4000, Carl Zeiss Inc.) was used to assess the thickness of retinal nerve fiber layer (RNFL), macular volume (MV), total macular thickness, mean and minimal ganglion cell-inner plexiform layer thickness (GC-IPL), optic cup volume and cup-to-disk ratio. Daily dosage of antipsychotic medication was calculated through chlorpromazine equivalents (CPZeq). Comparisons between the groups were performed with one-way ANOVA (Tukey post hoc), Student's t-test, and chi-squared test. Results: Sociodemographic/clinical characteristics of the groups were as follows: MC – age 29.6 ± 6.4 years; FC – age 32.8 ± 12.1 years; MP – age 33.2 ± 6.0 years (duration of illness 7.3 ± 4.0 years, CPZeq 254.1 ± 153.19 mg) and FP – age 30.6 ± 6.9 year (duration of illness 5.3 ± 3.7 years, CPZeq 201.6 ± 96.2 mg). There were no significant differences in any of the given parameters. Assessment of retinal parameters showed: lower macular central subfield thickness in the right eye when FP and FC were compared (243.75 vs. 260.52 µm, respectively; p=0.03), while in the left eye it showed a similar trend (FP vs. FC, 246.00 vs. 261.11 µm, respectively; p=0.06). MV was lower when FP and FC were compared both in the right (10.00 vs. 10.40 mm3, respectively; p=0.03) and in the left eye (9.94 vs. 10.40 mm3, respectively; p=0.00). Differences were found in total macular thickness in FP vs. FC in both right (277.81 vs. 288.94 µm, respectively; p=0.02) and left eye (276.00 vs. 288.88 µm, respectively; p=0.00). No significant differences in any of the retinal parameters were found when MP were compared with MC. In MP negative correlations were observed between mean antipsychotic dose and the following retinal parameters: inferior RNFL quadrant in the left eye (r=-0.76, p=0.00), macular volume in the right eye (r=-0.60, p=0.03), total macular thickness in the right (r=-0.61, p=0.03) and left eye (r=-0.59, p=0.04) and minimum GC-IPL thickness in the right eye (r=-0.63, p=0.02). In FP, no associations between any of the parameters and antipsychotic dosages were found. Discussion: To the best of our knowledge, relatively greater macular thinning in female patients with psychosis has not been reported before. Preclinical studies have shown that variability in individual retinal parameters could be influenced by the estrus cycle [3]. In this context, it has been suggested that women who are vulnerable to the development of PSD may have lower levels of endogenous estrogen in comparison to healthy women [4]. The importance of the menstrual phase in the interpretation of retinal thickness measurements in women during reproductive age is an important issue and should be taken into further consideration. Heterogeneous associations between antipsychotic dosages and retinal parameters need additional exploration. Further investigations of sex differences in PSD trough OCT-based measurements are needed in order to confirm and further clarify retinal sex differences in psychosis.